2006
DOI: 10.1073/pnas.0506954103
|View full text |Cite
|
Sign up to set email alerts
|

G o α regulates olfactory adaptation by antagonizing G q α-DAG signaling in Caenorhabditis elegans

Abstract: The heterotrimeric G protein Go is abundantly expressed in the mammalian nervous system and modulates neural activities in response to various ligands. However, G o's functions in living animals are less well understood. Here, we demonstrate that GOA-1 G o␣ has a fundamental role in olfactory adaptation in Caenorhabditis elegans. Impairment of GOA-1 G o␣ function and excessive activation of EGL-30 G q␣ cause a defect in adaptation to AWC-sensed odorants. These pathways antagonistically modulate olfactory adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 52 publications
4
85
2
1
Order By: Relevance
“…Previous reports suggest that mutation in goa-1 has a negative impact on egg laying, locomotion, and other normal behaviors of the worm (Matsuki et al 2006). With the downstream activator dgk-1, GOA-1 will inhibit the egl-30-mediated DAG pathway (Matsuki et al 2006;Avery and You 2012). During the initial hours of exposure (2 h), egl-8, egl-30 were downregulated, and dgk-1, goa-1 were upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports suggest that mutation in goa-1 has a negative impact on egg laying, locomotion, and other normal behaviors of the worm (Matsuki et al 2006). With the downstream activator dgk-1, GOA-1 will inhibit the egl-30-mediated DAG pathway (Matsuki et al 2006;Avery and You 2012). During the initial hours of exposure (2 h), egl-8, egl-30 were downregulated, and dgk-1, goa-1 were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…An ortholog of the heterotrimeric G protein alpha subunit Gq, egl-30, (Wang and Wadsworth 2002) and its downstream player, egl-8, (Ziegler et al 2009) in C. elegans plays a pivotal role in regulating pharyngeal pumping, egg laying and locomotion (Govorunova et al 2010). Previous reports suggest that mutation in goa-1 has a negative impact on egg laying, locomotion, and other normal behaviors of the worm (Matsuki et al 2006). With the downstream activator dgk-1, GOA-1 will inhibit the egl-30-mediated DAG pathway (Matsuki et al 2006;Avery and You 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular mechanisms of plasticity In addition to intracellular mechanisms, intercellular communication also plays an important role in regulating adaptation behaviors [147,161] (Fig. 3b).…”
Section: Modulation Of Chemosensory Behaviorsmentioning
confidence: 99%
“…We have reported that the insulin/PI3K (phosphatidyl inositol 3-kinase) signaling pathway, Go (GOA-1) and Gq (EGL-30) pathway, and HEN-1, a secretory protein with an LDL motif, regulate salt chemotaxis learning (4,11,12). The insulin-like signaling pathway and HEN-1 also regulate temperature learning (5,12).…”
mentioning
confidence: 99%